Adapting to climate change: Rapid response system - Kahilu, Darlington (Technical Centre for Agricultural and Rural Cooperation, 2011)
Farmers in Zambia with climate change questions can now receive quick answers via SMS from a new system developed by the country's National Agricultural Information Services